Current evidence demonstrates similar effects of kilohertz-frequency and low-frequency current on quadriceps evoked torque and discomfort in healthy individuals: a systematic review with meta-analysis. (17th November 2015) - da Silva, Vinicius Zacarias Maldaner; Durigan, João Luiz Quaglioti; Arena, Ross; de Noronha, Marcos; Gurney, Burke; Cipriano, Gerson
Abstract: Background : Neuromuscular electrical stimulation (NMES) is widely utilized to enhance muscle performance. However, the optimal NMES waveform with respect to treatment effect has not been established. Objective : To investigate the effects of kilohertz-frequency alternating current (KFAC) and low-frequency pulsed current (PC) on quadriceps evoked torque and self-reported discomfort. Data sources : PubMed, The Cochrane Library, EMBASE, MEDLINE, Physiotherapy Evidence Database (PEDro), SinoMed, ISI Web of Knowledge, and CINAHL were searched for randomized controlled trials (RCTs) and quasi-randomized controlled trials (QRCTs). Study selection : Two reviewers independently selected potential studies according to the inclusion criteria, extracted data, and assessed methodological quality. Data extraction and synthesis : Studies were eligible if they compared KFAC versus PC interventions. Studies that included outcome measures for percentage of maximal isometric voluntary contraction (%MIVC) torque and self-reported discomfort level were eligible for evaluation. Seven studies involving 127 individuals were included. The methodological quality of eligible trials was moderate, with a mean of 5 on the 10-point PEDro scale. Overall, PC was no better than KFAC in terms of evoked torque and there was no difference in self-reported discomfort level. Conclusion : KFAC and PC have similar effects on quadriceps evoked torque and self-reported discomfort level in healthy individuals. The small number and overall methodological quality of currently available studies included in this meta-analysis indicate that new RCTs are needed to better determine optimal NMES treatment parameters.